Pseudo — temporomandibular joint pain — dysfunction syndrome - Diakow, Peter RP (1988)
A case of pseudo TMJ-PDS is presented in which a classical sternomastoid trigger point syndrome mimicks dysfunction of the TMJ. Key points in the differential diagnosis are discussed.